Vagus nerve stimulation for the treatment of narcolepsy - Winter, Yaroslav; Sandner, Katharina; Bassetti, Claudio L. A.; Glaser, Martin; Ciolac, Dumitru; Ziebart, Andreas; Karakoyun, Ali; Saryyeva, Assel; Krauss, Joachim K.; Ringel, Florian; Groppa, Sergiu (Brain stimulation, 2024)
Background and objective - No study on neurostimulation in narcolepsy is available until now. Arousal- and wake-promoting effects of vagus nerve stimulation (VNS) have been demonstrated in animal experiments and are well-known as side effects of VNS therapy in epilepsy and depression. The objective was to evaluate the therapeutic effect of VNS on daily sleepiness and cataplexies in narcolepsy. - Methods - In our open-label prospective comparative study, we included narcolepsy patients who were treated with VNS because of depression or epilepsy and compared them to controls without narcolepsy treated with VNS for depression or epilepsy (18 patients in each group, aged 31.5 ± 8.2 years). We evaluated daily sleepiness (Epworth Sleepiness Scale, ESS) and the number of cataplexies per week before the implantation of VNS and at three and six month follow-ups. - Results - Compared to baseline (ESS: 15.9 ± 2.5) patients with narcolepsy showed a significant improvement on ESS after three months (11.2 ± 3.3, p < 0.05) and six months (9.6 ± 2.8, p < 0.001) and a trend to reduction of cataplexies. No significant ESS-improvement was observed in patients without narcolepsy (14.9 ± 3.9, 13.6 ± 3.7, 13.2 ± 3.5, p = 0.2 at baseline, three and six months, correspondingly). Side effects did not differ between the study groups. - Conclusion - In this first evaluation of VNS in narcolepsy, we found a significant improvement of daily sleepiness due to this type of neurostimulation. VNS could be a promising non-medical treatment in narcolepsy.